APPLICATION OF EXPLORATION APPROACH TO IMPROVE WRITING SKILLS TEXT PROCEDURES AND STUDENT CREATIVITY - Mulyandi Mulyandi; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2018)
Based on the above title the problem formulation as follows: 1) Is the writing skills of the text of the junior high school students whose learning using exploratory approach is better than using conventional methods? 2) Is the learning creativity of junior high school students whose learning using exploratory approach is better than conventional method? 3) Is there a relationship between students' learning creativity with text writing skills procedures? 4) How does the student picture at the time of writing text writing procedures? this study aims to obtain the results 1) to know the skills of writing scientific work of junior high school students whose learning using exploratory approach is better than using conventional methods. 2) to know the creativity of junior high school students whose learning using exploratory approach is better than a conventional method. 3) to find out the relationship between junior high school students' creativity with the skill of writing procedure text. 4) to know the description of students at the time of writing text writing procedures. The hypothesis of this study shows that the students' learning outcomes using exploratory approaches are better than conventional methods on Indonesian subjects regarding writing procedure text.